PENGARUH PERSEPSI GURU ATAS GAYA KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU AKUNTANSI SMK DI KOTA MADIUN - Titin Eka Ardiana (ITB AAS INDONESIA, 2016)
This study aims to determine: the influence of teachers perceptions on situational leadership style of theschool principal accounting teacher performance. This study uses a correlational study approach with samples taken from the accounting teacher in SMK Madiun incluster random sampling as much as 97 people. The variables of this study consists of one independent variables, namely: the perceptionof teachers on a situational leadership style of school head (X) and one dependent variable is: accounting teacher performance (Y). The data was collected using a structured question naire covered. Results of data collection were then analyze dusing regression analysis technique simple using SPSS version 20. The results show that: (1) perception of teachers on a situation a lleadership style of the principal and teacher performance category average accounting bothin the range of 50%, (2) the perception of teachers on a situational leadership style ofthe principal positive effect on teacher performance accounting with a contribution of 80,6%, remaining at 19,4% accounting teacher performance is determined by factors other than research. Keywords : teachers perceptions on situational leadership style of the school principal and teacher performance accounting